1971
DOI: 10.1104/pp.48.6.686
|View full text |Cite
|
Sign up to set email alerts
|

“Disaggregation” of Phytochrome in Vitro—A Consequence of Proteolysis

Abstract: The relationship between a large molecular weight (9S) and a small molecular weight (4.5S, 60,000 molecular weight) species of phytochrome was examined to determine if the larger species was an aggregate of the smaller. Alterations of pH, salt concentration, or phytochrome concentration did not cause any observable formation of the large form from the small form. However, in partially purified phytochrome extracts from Secale cereale L. and Avena sativa L., the large form was converted to the small form over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 38 publications
8
59
0
Order By: Relevance
“…There are data concerning the formation of small forms of animal ChE by treatment with proteases (12,26). Recently, Gardner et al (6) have reported an analogous situation for phytochrome, providing evidence that the small molecular weight form of phytochrome is a result of protease activity. The above data and the fact that treatment of the bean ChE with bacterial protease resulted in partial breakdown of the enzyme suggest that the smaller molecular weight form of the bean enzyme obtained by procedure II is due to proteolysis.…”
Section: Discussionmentioning
confidence: 92%
“…There are data concerning the formation of small forms of animal ChE by treatment with proteases (12,26). Recently, Gardner et al (6) have reported an analogous situation for phytochrome, providing evidence that the small molecular weight form of phytochrome is a result of protease activity. The above data and the fact that treatment of the bean ChE with bacterial protease resulted in partial breakdown of the enzyme suggest that the smaller molecular weight form of the bean enzyme obtained by procedure II is due to proteolysis.…”
Section: Discussionmentioning
confidence: 92%
“…We have attributed this discrepancy (5) to the protection against proteolysis afforded by our inclusion of the phenylmethylsulfonyl fluoride in the homogenization buffer. This compound is a potent inhibitor of proteases found in homogenates of grass seedlings (9).…”
Section: Resultsmentioning
confidence: 99%
“…The procedure does not change the recovery of auxinbinding sites compared to the previous procedure employing a mortar and pestle (unpublished results). The homogenization buffer was 50 mm Tris HC1, 1.0 mm Na2EDTA, 0.10 mm MgCl2, 14 mm 2-mercaptoethanol, 0.25 M sucrose (pH 8.0), normally saturated before use with phenylmethylsulfonylfluoride to retard proteolysis (9). The fluid was pressed through nylon cloth and microsomes were prepared by sequential sedimentation at 10,000g (10 min) and 48,000g (60 min) as previously described (5).…”
Section: Methodsmentioning
confidence: 99%
“…Both the coleoptiles and the primary leaves were used as starting material, since both contain the binding sites (24). Tissue was chopped and ground, as previously described (23), in one volume of homogenization buffer (50 mm Tris HCI, 1.0 mm disodium EDTA, 0.10 mM MgC62, 14 mM 2-mercaptoethanol, 0.25 M sucrose, (pH 8.0, normally saturated before use with PMSF3 to retard proteolytic degradation (8). After pressing the fluid through nylon cloth (2.7…”
Section: Methodsmentioning
confidence: 99%